La Sintesi del suono in Iannis Xenakis. Indagine di una ricerca compositiva - Di Scipio, Agostino (Musica/Tecnologia, 2023)
Unlike many composers of his generation, Iannis Xenakis personally devised and implemented the sound synthesis techniques used in some of his creative efforts. Eight of his works feature – in part or exclusively – sounds obtained with analogue or digital synthesis techniques, in a time span that goes from Analogique B (1959) to S.709 (1994). All of his electroacoustic music after La Légend d’Eer (1977) has sounds synthesized with computer technology. The sound synthesis procedures he devised, reflect peculiar operational and technological conditions, and indeed represent tokens of musical and sonological knowledge characteristic of a truly unique practice. In this paper we provide a survey of Xenakis’s efforts with sound synthesis, delineating their historical path through the experimenting of different technical contexts of material production and the corresponding theoretical and musical implications. Xenakis’ approach on sound synthesis is viewed as a domain of design of direct compositional relevance. Across subsequent steps in his carrier, Xenakis’s notion of ‘synthesis’ appears as a process or device generative of sound and music at once, in a single compact constructive gesture or strategy making it difficult to tell matter from form. Gradually, the musical work’s identity seemed to incorporate not just a specific linguistic-formal configuration, but the set of conditions of possibility elaborated by the composer – that is, eventually, the computer programming code (Gendy3, 1992). Iannis Xenakis’ commitment to crafting sound generation techniques – before using them to also craft music – witnesses at an attitude in which the appropriation of the material means of creative labour is an irreducible precondition for freedom of expression and musical aesthetics.